Public policy and long-term trends in inequality in rural China, 1988-2013 - Hisatoshi Hoken; Hiroshi Sato (The University of Western Ontario, Centre for Human Capital and Productivity (CHCP), 2017)
This study examines the long-term changes in the distribution of rural income in China from the late 1980s until the mid-2010s. The major findings are summarized as follows. First, contrasting trends are found in the contributions of agricultural income and wage earnings, which reflect the structural changes in rural income caused by the dual processes of economic development and systemic transition during the post-Mao era. Second, inequality in wealth is found to have become increasingly important for understanding rural inequality. Third, small but substantial improvements are found in the redistributive and poverty impacts of public transfers before and after implementation of the pro-rural public policies during the first decade of this century, representing a historical reversal in the long-term urban-biased public policy in contemporary China.
Keywords: D31; H23; O15; P25; 330; rural inequality; inequality decomposition; public transfers; public policy; China